Preliminary evaluation of the clinical implementation of cognitive-behavioral therapy for chronic pain management in pediatric sickle cell disease. (March 2020) - Sil, Soumitri; Lai, Kristina; Lee, Jennifer L.; Gilleland Marchak, Jordan; Thompson, Beth; Cohen, Lindsey; Lane, Peter; Dampier, Carlton
Highlights: Cognitive-behavioral therapy (CBT) for chronic pain was implemented in a naturalistic clinical setting for youth with SCD. Establishing care in CBT contributed to faster reductions in healthcare use over time compared to youth who do not initiate or establish care in CBT. Non-opioid therapies and non-pharmacological approaches need to be combined into multidisciplinary SCD care. Individualized, multidisciplinary care may offer the best health-related outcomes for youth with chronic SCD pain. Abstract: Objectives: Evaluate the implementation of cognitive-behavioral therapy (CBT) for chronic pain in a clinical setting by comparing youth with sickle cell disease (SCD) who initiated or did not initiate CBT. Design: Youth with SCD (ages 6–18; n = 101) referred for CBT for chronic pain were compared based on therapy attendance: Established Care; Early Termination; or Comparison (i.e., did not initiate CBT). Setting: Outpatient pediatric psychology and comprehensive SCD clinics in 3 locations at a southeastern children's hospital. Interventions: CBT delivery was standardized. Treatment plans were tailored to meet individualized needs. Main Outcome Measures: Healthcare utilization included pain-related inpatient admissions, total inpatient days, and emergency department reliance (EDR) at 12-months pre-post CBT. Patient-reported outcomes (PROs) included typical pain intensity, functional disability, and coping efficacy pre-post treatment. Results: Adjusting for age, genotype, and hydroxyurea, early terminators of CBT had increased rates of admissions and hospital days over time relative to comparisons; those who established care had faster reduction in admissions and hospital days over time relative to comparisons. EDR decreased by 0.08 over time for Established Care and reduced by 0.01 for every 1 completed session. Patients who completed pre- and post-treatment PROs reported decreases in typical pain intensity, functional disability, and improved coping efficacy. Conclusions: Establishing CBT care may support reductions in admissions for pain, length of stay, and EDR for youth with chronic SCD pain, which may be partially supported by patient-reported improvements in functioning, coping, and lower pain intensity following CBT. Enhancing clinical implementation of multidisciplinary treatments may optimize the health of these youth.